AL-JURJANI AND FUNCTIONALISM: A STYLISTIC INQUIRY INTO MODES OF MEANING (Journal of the College of Basic Education, 2022)
Metaphor is the most expressive and impressive power of style; it is the device that humans need to unravel incongruently their concepts and beliefs towards the physical world and the world of their own. Therefore, it has been investigated differently within different human fields. The study hypothesizes that Abdul- Qahir al-Jurjani ( 1010-1078), the Medieval Arab scholar, is the first functional stylistician whose interpretation of metaphor by using his notion of Construction has come closer to the European functional tradition, represented by MAK Halliday's (b.1925) Systemic Functional Linguistic(SFL). Al-Jurjani's coherent system of ideas has come to be referred to in the study as Construction Linguistic Theory (henceforth CLT). On a comparative ground, the study attempts to highlight the affinities and differences between the two linguistic paradigms. The study has recourse to al-Jurjani's main treatises, Dala'l al-I'jaz (Signs of Immutability) and Asrar al-Balagha (Secrets of Rhetoric), on the one hand, and Halliday's An Introduction to Functional Grammar (1985),on the other hand. Further references have been referred to.